The influence of digital transformational leadership on job performance: Job satisfaction and affective commitment as the intervening variables - Purba, Mien Shavero; Ardi, Ardi; Berlianto, Margaretha Pink (Institute of Computer Science (IOCS), 2023)
The era of digitalization demands changes in the way of work and work culture in various industries. This research aims to analyze several factors that can influence the job performance of marketing employee of PT XYZ North Jakarta. The factors analyzed in this study are digital transformational leadership, job satisfaction, and affective commitment. The study used purposive sampling and used questionnaires given directly to respondents. The data processing in this study uses Smart PLS 4.0 software. The results showed that digital transformational leadership has direct effect on job performance and job satisfaction, job satisfaction has direct effect on job performance and affective commitment. This study also found that job satisfaction has intervening effect on the relationship between digital transformational leadership and affective commitment and also between digital transformational leadership and job performance